Florfenicol-Polyarginine Conjugates Exhibit Promising Antibacterial Activity Against Resistant Strains - Li, Zhun; Yang, Ya-Jun; Qin, Zhe; Li, Shi-Hong; Bai, Li-Xia; Li, Jian-Yong; Liu, Xi-Wang (Frontiers in Chemistry, 2022)
Florfenicol was widely used as antibiotic in the livestock and poultry breeding industry, resulting in a serious problem of drug resistance. In order to solve the resistance of florfenicol, we designed and synthesized a series of florfenicol-polyarginine conjugates and tested for antimicrobial activities. Several conjugates showed excellent antibacterial activity toward drug-sensitive bacteria such as gram-negative bacteria Escherichia coli (E. coli) and gram-positive Staphylococcus aureus (S. aureus). These conjugates also exhibited strong activity against drug-resistant strains such as methicillin-resistant S. aureus (MRSA) and florfenicol resistant Escherichia coli strains (2017XJ30, 2019XJ20), one of which as conjugate E6 had 12.5 μmol/L of minimum inhibition concentration. These conjugates did not allow bacteria to develop resistance and were found to inhibit bacterial growth primarily by membrane depolarization and disruption. Additionally, florfenicol succinate (C1) showed certain activity after coupling with arginine. This suggested that conjugating arginine to florfenicol succinate effectively modulated the properties of prodrugs. These new conjugates may be further developed into a potential new class of broad-spectrum antibiotics or provide useful insights for expanding the pool of antibiotics.